Participation Constraints in Pension Systems - Roel Beetsma; Ward Romp (Tinbergen Institute, 2013)
We explore voluntary participation in pension arrangements. Individuals only participate when participation is more attractive than autarky. The bene??it of participation is that risks can be shared with future generations. We apply our analysis to a pay-as-you-go system, a funded system without buffers and a funded system with buffers. Buffers play a particularly interesting role, because they raise the sensitivity of the contributions to the asset returns. In particular, compared to a system without buffer requirements, they require higher contributions when asset returns are low. Moreover, individual contributions may be increasing or decreasing in the size of the young cohort, depending on whether the fund has more or less reserves than required. We con??ine ourselves to recursive settings and study equilibria characterised by thresholds on the contribution that young generations are prepared to make assuming that the future young apply the same threshold. For standard parameter settings two such equilibria exist, of which only the one with the higher threshold is consistent with the initial young being prepared to start the system. Finally, we explore the social welfare maximising policy parameter settings for various levels of uncertainty and risk aversion.
Keywords: E62; H55; 330; Participation constraints; pension funds; pay-as-you-go; buffers; risk-sharing; Umlageverfahren; Partizipation; Ökonomischer Anreiz; Gesetzliche Rentenversicherung; Generationengerechtigkeit